2015
DOI: 10.5424/sjar/2015133-7262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the growth and biomass production of Miscanthus sinensis, Miscanthus floridulus and Saccharum arundinaceum

Abstract: Miscanthus and Saccharum are considered excellent candidates for bioenergy feedstock production. A field experiment was conducted in Zhejiang province of China to characterize the phenotypic differences in three species, two of Miscanthus (M. sinensis and M. floridulus) and one of Saccharum (S. arundinaceum), each with two accessions collected from China. Agronomical traits, including plant height, culm number, tuft diameter and culm diameter, were monitored monthly for the first 3 years of growth. For each ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In this scenario, the use of perennial grasses for the lignocellulosic bioenergy production has gained more attention because of its abundancy, availability, regeneration capacity and ability to withstand drought (Wongwatanapaiboon et al 2012). S. arundinaceum, a perennial grass, has proved to be a promising bioenergy crop, which exhibits sustainable biomass yield (Feng et al 2015) and tolerance to salinity stress (Mirshad et al 2014). Now, the challenge is to find out perennial grass species that accumulate high biomass and at the same time that can be grown in various types of degraded land, so that the problem of its competition for land with that of food crops in arable land can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the use of perennial grasses for the lignocellulosic bioenergy production has gained more attention because of its abundancy, availability, regeneration capacity and ability to withstand drought (Wongwatanapaiboon et al 2012). S. arundinaceum, a perennial grass, has proved to be a promising bioenergy crop, which exhibits sustainable biomass yield (Feng et al 2015) and tolerance to salinity stress (Mirshad et al 2014). Now, the challenge is to find out perennial grass species that accumulate high biomass and at the same time that can be grown in various types of degraded land, so that the problem of its competition for land with that of food crops in arable land can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, heading date, culm length, culm diameter, and culm volume were the primary drivers of biomass yield for M. sacchariflorus (Table 6). Prior studies have also identified flowering time, culm length (or plant height), and stem thickness as important contributors to Miscanthus biomass yield (Clark et al, 2019; Clifton‐Brown et al, 2001; Feng et al, 2015; Jezowski, 2008; Lim et al, 2014; Yan et al, 2012; Zub et al, 2011). However, a novel insight from the current study was that variation among M. sacchariflorus genotypes for plant height and consequently yield was conferred primarily by the number of nodes and not internode length.…”
Section: Discussionmentioning
confidence: 99%
“…The SOC stock in SA is significantly higher than it in SG and MS, this is also mainly due to the high root weight and activity (Zhang et al, 2016). Although SA had the highest C sequestration potential, the aboveground dry matter was reported to be lower than that in MS and SG (Feng et al, 2015; Hou et al, 2015). According to our prior study, the fresh aboveground biomass yield of MS, SG, and SA was 4846.09 ± 963.58 g m −2 , 4566.83 ± 169.85 g m −2 , and 3772.72 ± 944.91 g m −2 , respectively.…”
Section: Discussionmentioning
confidence: 99%